2002
DOI: 10.1126/science.1071420
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic Metastasis in the Absence of Functional Intratumor Lymphatics

Abstract: Lymphatic metastasis contributes to mortality from solid tumors. Whether metastasizing cancer cells reach lymph nodes via intratumor lymphatic vessels is unknown. Here, we examine functional lymphatics associated with mouse tumors expressing normal or elevated levels of vascular endothelial growth factor-C (VEGF-C), a molecule that stimulates lymphangiogenesis. Although VEGF-C overexpression increased lymphatic surface area in the tumor margin and lymphatic metastasis, these tumors contained no functional lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

48
701
5
17

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 876 publications
(771 citation statements)
references
References 20 publications
48
701
5
17
Order By: Relevance
“…Studies that examined the physical dynamics of malignant proliferating tumors have shown that the intratumoral pressure is higher than that in the peritumoral area, which could cause collapse of the intratumoral lymph vessels. 28 This could then hamper invasion of lymph vessels by the invasive tumor cells. We and others had shown that intratumoral lymphatics with tumor emboli do exist; however, most of the LI lesions are located in peritumoral vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that examined the physical dynamics of malignant proliferating tumors have shown that the intratumoral pressure is higher than that in the peritumoral area, which could cause collapse of the intratumoral lymph vessels. 28 This could then hamper invasion of lymph vessels by the invasive tumor cells. We and others had shown that intratumoral lymphatics with tumor emboli do exist; however, most of the LI lesions are located in peritumoral vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies investigated lymphatics in xenografted sarcomas and reported that vessels were only found in peritumoural areas and absent from the intratumoural compartment [9,10]. With advances in imaging techniques, intratumoural lymphatics were detected and found to be functional, with tumour cells detected flowing within the vessels [11].…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies on xenografted tumours reported that lymphatics were only present in peritumoural areas and absent from the intratumoural compartment [9,10]. Such studies also suggested that these vessels were the main route for metastasis and that lymphangiogenesis did not seem to play a role in this process.…”
Section: Introduction and Aimsmentioning
confidence: 99%
“…The silencing mechanism is triggered by double-stranded RNA that causes specific degradation of the homologous target mRNA. [24][25][26][27] This new approach has been successfully applied to inhibit virus replication 28 and tumorigenicity. 29 Recent reports have described DNA vector-based strategies for delivery of small interfering RNA (siRNA) into mammalian cells.…”
Section: Introductionmentioning
confidence: 99%